Towards the goal of beautiful life - "Pai, Wamanrao" (Mumbai, 2011)
The book Towards the Goal of Beautiful Life offers teaching to the reader about the selection of the path to achieve success in life. This philosophy is a beautiful combination of worldly life and psycho spiritual psycho spiritual progress of Man and gives equal importance to both. it deals with the science of Art of living and has proved to be a boon to the poor masses, source of the strength to rich people and beneficial to the entire world.
Keywords: Philosophy